2016
DOI: 10.3390/photonics3010007
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Disinfection of Tap and Surface Water with Single High Power 285 nm LED and Square Quartz Tube

Abstract: Abstract:A small water disinfection system based on the combination of a strong single 25 mW LED with a wavelength of 285 nm and a short quartz tube with an outer rectangular cross section is presented. For the disinfection tests clear tap water and slightly turbid and yellow pond water are contaminated with high concentrations of Escherichia coli bacteria. These water samples are exposed to the germicidal 285 nm LED radiation while they flow through the quartz tube. The portion of surviving germs is determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…On the one hand, legionellae have the ability to repair this kind of DNA damage in the presence of light with the help of the enzyme photolyase [ 3 ], and on the other hand, the penetration depth of UV-C radiation in water is very low. Depending on the degree of contamination, it can be determined within the millimeter or centimeter range [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, legionellae have the ability to repair this kind of DNA damage in the presence of light with the help of the enzyme photolyase [ 3 ], and on the other hand, the penetration depth of UV-C radiation in water is very low. Depending on the degree of contamination, it can be determined within the millimeter or centimeter range [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sommer et al (1996) found that the use of an aluminum reflector increased the reduction equivalent fluence (REF) of a UV disinfection device by over 40% at a water UV transmittance (UVT) of 97%. Recently, with a rapid progress in UV light emitting diodes (UV-LEDs), UV reactors employing this new light source have been developed, and reflectors made of aluminum or other highly reflective materials have been applied to make the best use of UV radiation inside the reactor chamber (Hessling et al, 2016;Wurtele et al, 2011). Nevertheless, researches concerning how the reflected UV radiation contributes to the UV reactor performance are still very limited, compared to the abundant works discussing the effect of the reactor hydrodynamics (Sozzi and Taghipour, 2006a;Wols et al, 2011;Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultraviolet light has been proven to be effective for microbial inactivation by damaging bacterial DNA [ 13 , 14 , 15 ]. Pathogens absorb the ultraviolet (UV) light and thymine dimers are formed, blocking transcription and replication, which ultimately lead to cell death [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%